Randers Ricci soliton homogeneous nilmanifolds
Let F be a left-invariant Randers metric on a simply connected nilpotent Lie group N, induced by a left-invariant Riemannian metric a and a vector field X which is I_a (M)-invariant. We show that if the Ricci flow equation has a unique solution then, (N,F) is a Ricci soliton if and only if (N,F) is a semialgebraic Ricci soliton. , number=1, journal=MATHEMATICA SCANDINAVICA, author=Salimi Moghaddam, Hamid Reza, year=2021, month=Feb., pages=100–110